EDITORIAL (English) - Abar, Celina A. A. Pereira (Revista do Instituto GeoGebra Internacional de São Paulo, 2022)
The first issue of the volume 11, 2022, presents seven articles seeking to encompass the different possibilities and paths with the GeoGebra can be investigated.